Hydrothermal synthesis of Nd3+-doped heterojunction ms/tz-BiVO4 and its enhanced photocatalytic performance. (June 2018) - Chen, Ruizhi; Wang, Weixuan; Jiang, Dongmei; Chu, Xiaoxuan; Ma, Xueming; Zhan, Qingfeng
Abstract: BiVO4 photocatalysts with different Nd 3+ doping content were prepared by a hydrothermal method with varied hydrothermal reaction time. The effects of Nd 3+ doping on phase transformation, morphology, chemical valence, optical properties and photocatalytic activities were investigated. With different reaction time, phase transformation from tetragonal zircon (tz-BiVO4 ) to monoclinic scheelite (ms-BiVO4 ) could be found, and Nd 3+ doping played a suppressive role in this process. Scanning electron microscopy showed the morphology evolved from irregular structure to rod-like shapes with phase transformation. The photoluminescence induced by Nd 3+ doping could be confirmed by UV–vis diffuse reflectance spectra. Photocatalytic performance tests had been performed under simulated solar conditions and sample with 1 at% Nd 3+ doping and 5 h reaction time showed the best performance (89% degradation rate in 90 min). The pH also showed great influence on morphology and phase transformation of samples. Finally, the phyotocatalytic mechanism and effects of Nd 3+ in phase transformation were discussed. Highlights: 1. Nd 3+ doped BiVO4 product with heterojunction structure was first prepared by a hydrothermal reaction. 2. The phase transformation from monoclinic scheelite to tetragonal zircon could be perceived and the role of Nd 3+ doping in this process was discussed. 3. The effect of pH on phase transformation and sample morphology was investigated. 4. The photocatalytic performance was greatly improved by doping, photoluminescence and heterojunction.